Let's do those 60 minutes! Children's perceived landscape for daily physical activity. Issue 4 (3rd May 2020) - Högman, Johan; Augustsson, Christian; Hedström, Pernilla
ABSTRACT: In a scientific effort to understand the reasons for low physical-activity levels among children, there is a need to consider how children perceive and interact with their complex environments holistically. This study outlines an image of the perceived landscape within which children in two lower-socioeconomic contexts engage in daily physical activity. By applying bioecological perspectives (Bronfenbrenner, U. 2005. Making human Beings human: Bioecological perspectives on human development . SAGE), the aim included an analysis of how the perceived landscape and its interrelated factors influence children's physical activity. We used 15 focus-group interviews with children ( n  = 63, ages 8–13) from four different rural and suburban areas of southern and central Sweden. Through analyzing the children's stories about their experiences of everyday physical activity from a bioecological perspective, an image of a complex landscape was revealed. Structural (schools' institutional frameworks), cultural (local sports cultures), and environmental factors (e.g. schoolyard design) were evident in interpersonal relations within the microsystem and interacted with personal characteristics, primarily gender and level of physical competence and, thereby, affected the possibilities of the children engaging in proximal processes related to physical activity. This study contributes new qualitative understanding based on children's voices about how the performance of daily physical activity among younger children (ages 7–13) in lower-socioeconomic areas may be considered an interactional process between individuals and their perceived environment, which can be thought of as a multidimensional landscape. Implications include actions which contribute to more diverse environments enabling proximal processes among a broader group of children.